Physiological bases for understanding estrous cycle differences between bos taurus and bos indicus - Sartori, Roberto; Bastos, Michele Ricieri [UNESP]; Mattos, Maria Clara Costa [UNESP] (My University, 2010)
Background: Although there is some information in the literature discussing differences of the estrous cycle of Bos taurus and Bos indicus cattle, most of the data derive from studies performed in temperate climate countries, under environmental and nutritional conditions very different than those found in tropical countries. Moreover, the physiological basis for understanding the differences between Bos taurus and Bos indicus estrous cycles are still unknown. This review explores the physiological and metabolic bases for understanding the key differences between the Bos taurus and Bos indicus estrous cycle. Moreover, it presents recent results of studies that have directly compared reproductive variables between Zebu and European cattle. Review: The knowledge of reproductive physiology, especially the differences between Bos taurus and Bos indicus, is important for the development and application of different techniques of reproductive management in cattle. In this regard, overall, Bos indicus have a greater number of small ovarian follicles and ovulatory follicles are smaller as compared to Bos taurus. Consequently, Zebu cattle also have smaller corpus luteum (CL). Nevertheless, circulating concentrations of steroid and metabolic hormones are not necessarily higher in European cattle. In fact, some studies have shown that despite ovulating smaller follicles and having smaller CL, Bos indicus cows or heifers have higher circulating concentrations of estradiol, progesterone, insulin and IGF-I compared to Bos taurus females. In addition, there are also substantial differences between Bos indicus and Bos taurus cattle in relation to follicle size at the time of selection of the dominant follicle. Conclusion: Data from very recent studies performed in Brazil have corroborated results from previous reports that have observed substantial differences in the estrous cycle variables of Bos indicus versus Bos taurus cattle. Those differences are probably related to distinct metabolism and metabolic hormone concentrations between Zebu and European cattle. This increased knowledge will allow for the establishment of more adequate reproductive management protocols in both breeds of cattle.
Keywords: Bos indicus; Bos taurus; Heat stress; Metabolic hormones; Reproductive physiology; Steroid hormones; Bos